Art of philosophy : a selection of Jerzy Perzanowski's works - Perzanowski, Jerzy (Categories (Frankfurt am Main, Germany), 2012)
Jerzy Perzanowski's ideas were based on an original blend of logic and ontology in what he called onto/logic, where the slash is meant to suggest a quotient of ontology by logic. Perzanowski began as a logician, his early works being on modal logic, then gradually shifted his interest to "logical philosophy", meaning not so much philosophy of logic as philosophy informed by logic. Perzanowski was a rare breed of analytical philosopher who thought that a philosophical "theory of everything" was worthwhile. In this systematic spirit, he began with method. He presented his "method of total analys.